2004
DOI: 10.1136/bmj.329.7465.533
|View full text |Cite
|
Sign up to set email alerts
|

Isolation measures in the hospital management of methicillin resistant Staphylococcus aureus (MRSA): systematic review of the literature

Abstract: Objective To evaluate the evidence for the effectiveness of isolation measures in reducing the incidence of methicillin resistant Staphylococcus aureus (MRSA) colonisation and infection in hospital inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
204
0
12

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(223 citation statements)
references
References 62 publications
4
204
0
12
Order By: Relevance
“…However, adherence to current guidelines, with isolation measures to reduce MRSA transmission, is supported by a recent systematic review. 17 Even as outpatients, attending the clinic or day unit, problems are encountered with patients requiring special 'areas' in which to be assessed, again not practical in many settings. Guidelines from the CDC 8 suggest that in centres where MRSA is problematic, patients should be treated as a cohort; however, a recent paper in The Lancet suggested that in the Intensive Therapy Unit setting, moving patients into single rooms or cohorted bays was not associated with a reduction in crossinfection.…”
Section: Discussionmentioning
confidence: 99%
“…However, adherence to current guidelines, with isolation measures to reduce MRSA transmission, is supported by a recent systematic review. 17 Even as outpatients, attending the clinic or day unit, problems are encountered with patients requiring special 'areas' in which to be assessed, again not practical in many settings. Guidelines from the CDC 8 suggest that in centres where MRSA is problematic, patients should be treated as a cohort; however, a recent paper in The Lancet suggested that in the Intensive Therapy Unit setting, moving patients into single rooms or cohorted bays was not associated with a reduction in crossinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Early contact isolation of patients colonized or infected with MRSA/VRE can limit their spread [2,3]. Consequently, most institutions try to identify and contact isolate these patients as early as possible during the admission process.…”
Section: A Introductionmentioning
confidence: 99%
“…However, studies on control measures are limited [3] and evidence for their effectiveness sparse and often contradictory [4]. Current guidelines are based on medical and scientific rationale and suggestive evidence rather than study results [4].…”
Section: Introductionmentioning
confidence: 99%